THE ROLE OF INTERCROPPING IN THE PRODUCTION OF BALANCED FEED [Text] - Nasiyev, B. N.; Zhanatalapov, N. Zh (Science and education №1, 2018)
In only within for 5 years in the Republic of Kazakhstan it is planned to construct about 60 feedlots with single keeping of 150 thousand heads or 300 thousand heads a year. Now in feeding complexes young growth is grown up and fattened in the extensive way on unbalanced diets that leads to large expenses of forages and work for gain unit. Therefore one of the important conditions of further increase in beef production is the development of effective technologies of providing feeding complexes and farms of industrial type with own food supply, at economical expenditure of fodder grain. Всего за 5 лет в Республике Казахстан планируется построить до 60 откормочных площадок с единовременным содержанием 150 тыс. голов или 300 тыс. голов в год. В настоящее время в откормочных комплексах выращивают и откармливают молодняк экстенсивным путем на несбалансированных рационах, что ведет к большим затратам кормов и труда на единицу прироста. Поэтому одним из важных условий дальнейшего увеличения производства говядины является разработка эффективных технологии обеспечения откормочных комплексов и ферм промышленного типа собственной кормовой базой, при экономном расходовании фуражного зерна.
Keywords: рк -- отечественное издание -- научный журнал -- периодическое издание -- кормовая база -- фуражное зерно -- кормление молодняков -- кормовые угодья; рк -- отечественное издание -- научный журнал -- периодическое издание -- кормовая база -- фуражное зерно -- кормление молодняков -- кормовые угодья; научный журнал; периодическое издание; кормовая база; фуражное зерно; кормление молодняков; кормовые угодья